Adaptive tasks: school transition from the 5th to 6th grade of elementary education - Cassoni,Cynthia (2020)
Abstract Within the ages of ten and thirteen years, children experience changes in elementary school. Focusing on students from public schools, the aim of this study was to investigate whether, from the 5th to 6th grade, they change indicators of performance, social skills, self-satisfaction and support network, self-concept and stress dimensions from one grade to another. A total of 379 students (212 girls), with a mean age of 10.6 years (SD = 0.91), participated at the beginning of the study. Instruments: Social Skills Assessment System; Child Stress Scale; Proof Brazil; Questionnaire for Self-Concept Evaluation; Multidimensional Scale of Life Satisfaction for Children. The results indicate a decrease in social skills, self-concept and life satisfaction; indicators of stress symptoms and academic performance increased from the 5th to 6th grade. The results are partially in agreement with previous findings of adverse effects of transition.